Impact of Power-On Duration on Chloride Migration in Reinforced Reactive Powder Concrete with Recycled Aggregates, Fly Ash and Silica Fume - Yoobanpot, Naphol; Hengterm, Pannaphat; Makul, Natt Makul; Sua-Iam, Gritsada (Science & Technology Asia, 2024)
This study aimed to examine the chloride migration characteristics of Reinforced Reactive Powder Concrete (RRPC) that is not in a steady state. The RRPC was formulated using pozzolans and recycled concrete aggregate (RCA). The study was mostly looking at how the chloride migration coefficient changed when two important things happened: how long the power was on and how much RCA was in the RRPC mixtures. Six separate categories of RRPC mixtures were formulated, each containing different ratios of silica fume (SF) and fly ash (FA), as well as varying amounts of RCA substituting for the traditional coarse aggregate. The results of this study uncovered a significant trend in the chloride migration coefficient as the duration of power on increased from 12 to 36 h. The coefficient first showed an upward trend, then a downward trend. This trend indicates the existence of a curative and sealing mechanism within the concrete structure, which gradually improves its ability to resist the penetration of chloride over time. Adding RCA to reinforced reactive powder concrete (RRPC) mixtures also slowed down the movement of chloride, and the effect became more obvious as the RCA content increased. It also found that the effect of RCA content on chloride resistance was more noticeable during shorter durations but became less significant as the duration increased.